Staying alive after 35 the bare essentials - McClelland, Tony (Tfm Pub., 2004)
Although written to provide the perfect medical advice manual for the lay public, the book is an excellent source of current medical knowledge, relating to the common diseases, and provokes and challenges in such a way, that it is likely to be widely read by the profession at large.